Factors influencing the involvement of Malaysian youth in entrepreneurship / Nor Hidayah Harun ... [et al.] - Harun, Nor Hidayah; Johar, Norchahaya; Maliki, Marinah (2014)
This study attempts to investigate the factors influencing the involvement of Malaysian youth in entrepreneurship. A total of 200 youth entrepreneurs ages between 15 to 35 years old from various states in Malaysia are randomly selected as respondents. The influencing factors such as environment, family, financial literacy and personal characteristics have been analyzed as the predictor to the youth involvement in entrepreneurship. Descriptive analysis is used to describe the profile of the respondents, while the relationship between the predictors is tested empirically using Pearson correlation analysis, and regression analysis is employed in order to determine the most influencing factor that contribute to the youth involvement in entrepreneurship. The findings reveal that all the predictors have a positive relationship with Malaysian youth's involvement in entrepreneurship except for the financial literacy. The regression analysis also indicates that the personal characteristic of the youth is the main influencing factor that contributes to the involvement in entrepreneurship. This study is expected to motivate the youth to be entrepreneur so as to boost economic growth and lessen unemployment rate in Malaysia.